1999
DOI: 10.1148/radiographics.19.3.g99ma05655
|View full text |Cite
|
Sign up to set email alerts
|

Imaging Features of Avulsion Injuries

Abstract: Avulsion injuries are common among participants in organized sports, especially among adolescent participants. Imaging features of both acute and chronic avulsion injuries of the pelvis, knee, ankle and foot, shoulder, and elbow were evaluated to help distinguish these injuries from more serious disease processes such as neoplasm and infection. At radiography, acute injuries (ie, those resulting from extreme, unbalanced, often eccentric muscular contractions) may be associated with avulsed bone fragments, wher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
142
0
8

Year Published

2003
2003
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 261 publications
(164 citation statements)
references
References 46 publications
(62 reference statements)
3
142
0
8
Order By: Relevance
“…6 Moreover, unrecognized and untreated anterolateral instability may lead to osteoarthritis or the failure of surgical reconstruction of the ACL. 9 In the acute stage of the avulsion fracture, clinical evaluation of the knee may be difficult because of pain, muscle spasm, hemarthrosis, and soft tissue edema.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…6 Moreover, unrecognized and untreated anterolateral instability may lead to osteoarthritis or the failure of surgical reconstruction of the ACL. 9 In the acute stage of the avulsion fracture, clinical evaluation of the knee may be difficult because of pain, muscle spasm, hemarthrosis, and soft tissue edema.…”
Section: Discussionmentioning
confidence: 99%
“…The Segond fracture was previously thought to result from an avulsion fracture at the insertion of the middle portion of the lateral joint capsule, also called the LCL, of the knee. [1][2][3][4][5][6] In this regard, Weber and colleagues collateral ligament in an oblique fashion to insert at the midportion of the lateral tibia, posterior to the LCL; and fourth, an attachment of these structures connected to each other at the typical site of the Segond fracture (ie, the lateral tibial rim). These authors suggested that, in addition to the LCL, fibers of the iliotibial tract and the AOB are important factors in the pathogenesis of the Segond fracture.…”
Section: Discussionmentioning
confidence: 99%
“…The injury leads to partial or complete detachment of the apophysis onto which the tendon is attached. Acute apophyseal injuries can be subdivided into major and minor based on the degree of dislocation of the apophyseal fragment [6]. Major apophyseal lesions cause dislocation of the avulsed fragment at an extent that precludes resorption.…”
Section: Apophyseal Injuriesmentioning
confidence: 99%
“…Medial epicondylar avulsion is also frequently seen with posterolateral dislocation of the elbow. In valgus stress, the medial joint space is temporarily opened, and at times the avulsed fragment is trapped within the joint [13]. In acute avulsions, US reveals local soft-tissue swelling and separation of the medial epicondyle.…”
Section: Traumatic Pathologymentioning
confidence: 99%